Learning to control potato late blight. A facilitator's guide. - Caceres, P.A.; Pumisacho, M.; Forbes, G.; Andrade-Piedra, J.L. (International Potato Center, 2008)
This guide is designed to provide instructions to facilitators involved in building capacity of small-scale farmers to control late blight. It is divided into five learning modules. Each module deals with one competency that farmers need to control late blight effectively.